Equatorial grooves distribution on Ganymede: Length and self-similar clustering analysis. (January 2021) - Lucchetti, A.; Rossi, C.; Mazzarini, F.; Pajola, M.; Pozzobon, R.; Massironi, M.; Cremonese, G.
Abstract: Grooves represent the evidence of tectonic activity that deformed Ganymede surface during its geologic evolution. In this work, we investigate the main characteristics of Ganymede's groove populations on four different areas located at the equatorial region of the satellite (Uruk Sulcus, Babylon Sulci, Phrygia Sulcus and Mysia Sulci). Specifically, we analyse i) the grooves length distribution to provide a framework for their evolution and ii) the grooves self-similar clustering to infer their vertical penetration inside Ganymede icy shell. For each dataset, we find that the grooves distribution is well fitted by an exponential-law and a power-law distribution depending on the structure length. This implies the presence of confined structures in a shallow layer of the icy crust (relatively shorter, exponentially-fitted structures) and crustal-scale structures that could theoretically reach the crust-ocean interface (relatively longer, power law-fitted structures). In addition, the existence of two exponential distributions for few datasets suggest that there could be two different system of structure confined within specific mechanical crust layers. The thickness of the penetrated icy shell is retrieved through the self-similar clustering analysis and ranges between 105 and 130 ​km for the examined datasets. This value agrees with independent estimates of the icy shell thickness, ranging between 80 and 150 ​km. Moreover, our results support the hypothesis that a large number of grooves penetrate the brittle icy crust, with sets of fractures vertically confined in different mechanical layers, while the penetration of few interconnected faults underlying longer grooves may interest the whole icy crust above the liquid ocean. Highlights: Ganymede's grooves are the representation of a hierarchical system. Shorter grooves are vertically confined in the brittle icy crust. Longer grooves are crustal-scale structures theoretically reaching the crust-ocean interface. The icy shell thickness interested by grooves penetration is between 105 and 130 ​km.